Convective heat transfer in MHD hybrid nanofluid flow over two different geometries. (October 2021) - Ashwinkumar, G.P.; Samrat, S.P.; Sandeep, N.
Abstract: In this paper, we examined the significance of nonlinear thermal radiation on 2-D magnetohydrodynamic flow of hybrid nanoliquid across two distinct geometries. The hybridized nanoliquid is encompassed with CuO and Al2 O3 nanomaterials suspended in the base liquid (water). The suitable similarity transmutations are utilized to convert the PDE's to the non-dimensional ODE's and solved them by employing Runge-Kutta method with shooting procedure. Further, simultaneous solutions are witnessed for flow over cone case and plate case respectively. The stimulus of dimensionless parameters on velocity and thermal fields are discussed thru plots, further, the wall friction and local Nusselt number are presented thru the tables. The results reveal that, the nonlinear thermal radiation has a propensity to boosts the thermal distributions and to decays the rate of heat transfer. The flow and thermal distributions are significant in flow over a plate as compared with flow over a cone case. Moreover, the thermal transport rate of the flow above a cone is considerably advanced than that of flow over a plate.